(untitled) (African Human Mobility Review, 2021)
This paper examines the challenges to the implementation of the Economic Community of West African States (ECOWAS) Protocol on Free Movement, with particular reference to Ghana and Sierra Leone. The paper is based on a desktop review and in-depth interviews with selected ECOWAS migrants and officials of institutions responsible for managing migration in Ghana and Sierra Leone. The findings suggest that Ghana and Sierra Leone have made modest progress in the implementation of the protocol. Apart from abolishing visa and entry requirements for 90 days, both countries have adopted the standardized ECOWAS Travel Certificate. Despite a few achievements, the following challenges affect the implementation of the free movement protocol in both countries: Policy ambiguities resulting from contradictions between national laws on employment and the ECOWAS Free Movement Protocol; harassment of migrants; migrants’ lack of travel documents; low level of knowledge about the ECOWAS protocol; resource constraints; fears of competition with immigrants, especially in Ghana; securitization of migration and migrants; weak labour market and migration information systems, economic challenges and political instability. This paper concludes that the future implementation outcomes of the ECOWAS protocol largely depend on the commitment of the member states and financial support that they receive from ECOWAS and its development partners.